Disseminated Talaromyces marneffei Infection in a Non-HIV Infant With a Homozygous Private Variant of RELB - Ding, Xiaofang; Huang, Han; Zhong, Lili; Chen, Min; Peng, Fang; Zhang, Bing; Cui, Xinyu; Yang, Xiu-An (Frontiers in Cellular and Infection Microbiology, 2021)
Objective This study presents a relatively rare case of disseminated Talaromyces marneffei (T. marneffei) infection in an HIV-negative patient. Methods An 8-month-old girl was hospitalized because of uncontrollable fever and cough for 6 days. Routine laboratory tests, biochemical detection, immunological tests, pathogenic examination, and imaging inspection were performed. Genetic tests of trio whole genome sequencing (Trio-WES), trio copy number sequencing (Trio-CNVseq), and Sanger sequencing were conducted to identify pathogenic variants. In silico analysis of the sequence alignment and structural modeling results was carried out to study the possible pathogenicity of the identified variant. Western blotting was performed to investigate the expression of the identified gene at the protein level. Results Enhanced CT and MRI scanning demonstrated thymic dysplasia, diffuse pulmonary and liver nodules, and many balloon-like air sacs in both lungs. The white blood cell count, neutrophil count, and neutrophil ratio were normal or elevated. The patient was HIV-negative and bone marrow and blood culture showed T. marneffei infection. Total lymphocyte count, CD3+ T lymphocyte count, CD3+CD4+ T lymphocyte count, CD3+CD8+ T lymphocyte count, and NK cell count decreased, while the number of CD19 positive B cells increased. However, the ratio of CD3+CD4+:CD3+CD8+ T cells increased. Trio-WES identified a homozygous private variant of NM_006509: c.400_c.401insAGC/p.Lys134 delinsLysGln in RELB and Sanger sequencing validated the result. Structural modeling indicated that the variant may be pathogenic. Reverse transcription-polymerase chain reaction and Western blot analysis showed that the expression of RelB in the patient was lower than that in the healthy controls at mRNA and protein levels. Conclusion This is the first report on disseminated T. marneffei infection in a patient with a homozygous private variant of RELB.